The Face of the Firm: The Influence of CEOs on Corporate Reputation - Love, E. Geoffrey; Lim, Jaegoo; Bednar, Michael K. (Academy of Management Journal, 2017)
It is widely assumed that CEOs shape how people view firms, but the question of how these leaders influence corporate reputations has received little theoretical or empirical attention. This study addresses two core questions in this vein: to what degree do leaders really matter for firm reputation, and which leaders affect their firm’s reputation? We develop theory to explain how and why leaders should enter into evaluations of the firms that they lead. Specifically, we propose that CEOs’ effects on corporate reputation will depend on leader prominence and on perceptions of leader quality. We thus test hypotheses that examine how CEOs’ media coverage, industry awards, and outsider standing affect the reputations of their firms. Our findings indicate that highly regarded CEOs enhance their firms’ reputations, sometimes substantially, and CEOs who receive negative press coverage damage their firms’ reputations. However, CEO prominence alone is not associated with higher firm reputation. We discuss implications for research on top leaders and corporate reputations.